Analisis Produktivitas Pengupasan (Overburden) Pada Penambangan Batubara di PIT Tal Utara Barat PT Bukit Asam, Tbk. Tanjung Enim, Sumatera Selatan - Al Fahri, Imam; Gumanti, Suhardiman; Husni , Ahmad (Jurnal Inovasi Global, 2025)
This study aims to analyze work efficiency, productivity of loading and unloading equipment, productivity of hauling equipment, and Match Factor in overburden stripping activities at the North West Pit Tal, Air Laya Mine of PT Bukit Asam, Tbk. Overburden stripping activities are an important part of mining operations that require good coordination between loading and unloading equipment to achieve optimal efficiency and productivity. This study was conducted by directly observing mining operations and analyzing operational data from PT Bukit Asam, Tbk in collaboration with PT Antareja Mahada Makmur (AMM), as its mining contractor. The results showed that the productivity of the Caterpillar 395 excavator was 504.43 tons/hour, while the productivity of the Heavy Duty 785 was 49.46 tons/hour. The match factor value of 0.68 indicates an imbalance in the work synchronization between the loading and unloading equipment. To achieve optimal work harmony (match factor approaching 1), repair slippery and uneven roads to increase the match factor of the loading and transporting equipment used at the research location so that the working time of the loading and transporting equipment is more optimal.